2012
DOI: 10.4314/ajtcam.v10i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulating Effect of Aqueous Extract of <em>Amphypterygium Adstringens</em> on Immune Cellular Response in Immunosuppressed Mice

Abstract: Amphypterygium adstringens is a Mexican tree known as cuachalalate whose bark is habitually used for the treatment of fresh wounds, gastric ulcers, gastrointestinal cancer and various inflammatory conditions. The aim of this study was to evaluate the immunostimulant effect of the aqueous extract of A. adstringens on immune cellular response in immunosuppressed mice. An aqueous extract from the bark of cuachalalate was administered into BALB/c mice for 10 days. We assessed their immunostimmulant activity on cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Furthermore, although there are few studies on the anticancer properties of the aqueous extract of the stem bark, ability to restore the immunological parameters of immunocompromised mice with L5178Y lymphoma has been reported. Moreover, oral administration of the extract for ten days (10 and 100 mg/kg) induced an increase in the immune cell response and the proliferation of splenocytes in the animals [50].…”
Section: Anticancermentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, although there are few studies on the anticancer properties of the aqueous extract of the stem bark, ability to restore the immunological parameters of immunocompromised mice with L5178Y lymphoma has been reported. Moreover, oral administration of the extract for ten days (10 and 100 mg/kg) induced an increase in the immune cell response and the proliferation of splenocytes in the animals [50].…”
Section: Anticancermentioning
confidence: 94%
“…Masticadienonic and 3α-hydroxymasticadienonic acids were isolated from the hexane extract, which inhibited the growth of five human cancer cell lines and stimulated nitric oxide production in macrophages [7]. Recently, it was reported that 3α-hydroxymasticadienonic acid induced the maturation of dendritic cells, which present antigens and are involved in the T lymphocyte activation [9,50]. Interestingly, the coadministration of dendritic cells with triterpene to melanoma mice decreased tumor growth and increased the area of cell death in tumors [9].…”
Section: Anticancermentioning
confidence: 99%
“…Carlowrightia cordifolia showed poor immunostimulatory effects [ 17 ]. Amphipterygium adstringens showed in vivo immunostimulatory effects [ 51 ], whereas masticadienonic acid ( Figure 1 ), its active compound at 0.001 μ M, increased the NO production (1.8 fold) with higher activity compared to 0.001 μ M ursolic acid (1.4 fold) [ 55 ]. Uncaria tomentosa showed in vitro immunostimulatory effects [ 50 ], whereas pteridine ( Figure 1 ), its active compound, tested at 600 mg/kg i.p., increased the lymphocyte proliferation in immunocompetent mice [ 59 ].…”
Section: Further Considerationsmentioning
confidence: 99%
“…Actinoplanes sp. was isolated from Amphipterygium adstringens (K. Rodríguez-Peña, M. Macías-Rubalcava, L. Rocha Zavaleta, R. Rodríguez-Sanoja, S. Sanchez, unpublished data), a medicinal plant that exhibits a broad range of biological properties, including antitumor, antimicrobial, and anti-inflammatory activities ( 3 5 ). Furthermore, Actinoplanes spp.…”
Section: Genome Announcementmentioning
confidence: 99%